A review on economics of power quality: Impact, assessment and mitigation. (May 2018) - Sharma, A.; Rajpurohit, B.S.; Singh, S.N.
Abstract: The quality of electrical power supply directly influence the function and operation of the electrical devices feed by the electrical power system distribution network. Poor power quality(PQ) can cause peculiar operation of electrical devices which causes heavy economic loss to the customer and network operator. Poor PQ includes many phenomenon in which some are; voltage sag and interruptions, harmonics, surges, flickers, etc., and for each phenomenon the behaviour of electrical devices varies, which makes the quantification of losses due to poor PQ a complex subject. Among various PQ problems, voltage sag is more focussed by researchers from the mid of 90 s, because voltage sag directly affect the operation of electrical devices by causing interruptions (either small or large) in the process which further causes heavy economic losses. But the input (information) needed to quantify economic loss due to poor PQ varies from one method to other, and this makes a need to study the proposed methods and come to a meaningful conclusion. Quantification of cost of poor PQ (except voltage sag) is a research topic which has to be addressed to know the need of expenditure for smooth power supply. This research work includes some case studies to show the effect of PQ problems in various regions of the world. The paper includes a discussion on various indices and methodologies proposed by researchers in past to quantify PQ phenomenon, and some curves which shows the sensitivity of various equipments towards PQ problems. In this work one method is proposed for voltage sag cost calculation. At the end, proposed solutions of poor PQ problems and their implementation costs are also discussed and concluding remarks for the study is presented.